Preventive Measures Against Infectious Diseases and the Teachings of The Prophet (S.A.W) - Dr. Muhammad Abubakar Siddique; Prof. Dr. Shah Mueen ud Din Hashmi (jihat-ul-islam, 2022)
Humanity has been suffering from epidemics since ancient times. Infectious diseases are sometimes caused by the excesses and imbalances of human society and sometimes by changes in the nature. We can find some traces of epidemics in the Prophetic and Righteous Caliphs era, which shows that natural disasters also existed in the Prophetic era and efforts were also made during the Prophet's time to prevent and eradicate epidemic diseases. In this regard there are clear teachings exist in the Qur'an and Sunnah. In the present era, the trend of Study of Sirah is increasing day by day. Therefore, it has become an important need to clarify the usefulness and meaningfulness of Sirah in relation to contemporary issues. Based on this, the study of Sirah is very important in the field of epidemic diseases. We have recently faced Corona pandemic and medical science guidelines for preventing corona have been implemented by the governments. Although it was a purely medical problem and medical experts/scientists have done a lot of work on it. But the similarity between the instructions given by medical experts/scientists and the teachings of the Qur'an and Sunnah demands the deep study of Islamic teachings on epidemic diseases to clarify the usefulness of these teachings in the current situation. The study of precautionary measures to prevent infectious diseases, in the light of the teachings of the Prophet, is also important in the sense that there is a scholarly debate on the conflict between science and religion in the present age. This is the age of the rise of medical science, so the question that has rightly arisen in the minds of educated people is, how similar are the facts proved by medical science and Islamic teachings? Are these facts consistent with or contradictory to Islamic teachings? This is a long discussion; this article is only the study of & comparison between the teachings of Prophet ﷺ on preventive measures against infectious diseases and the suggestions of modern medical science.